Women's movement in Malaysia : a study of the Sisters in Islam - Ishaq Hanis bin Asmail (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2015)
This study examines reform approaches adopted by Sisters In Islam in Malaysia. It analyzes the methods they used and the strategies they deployed over the year of its establishment. This study is generally divided into two major approaches: practical (external) and theoretical (internal) approach. The data collected from this study suggest that the group has not only restricted itself to the appeal of rights of Muslim women, but has extended beyond the women issues. This study finds that the Sisters In Islam (SIS) possesses Western feminism's cell which is not totally compatible with the mainstream teachings of Islam (ahl al-sunnah wa al-jamā'ah). Liberalism in thought and practice has consequently made their action irresponsible to the system and religious practices in Malaysia. The contents of the thesis are divided into four main chapters. The first chapter is an introduction to the whole framework and idea of this study. The second introduces a brief background to the Sisters In Islam. The third chapter discusses the first layer of the approaches while the fourth elaborates the second layer or the internal foundation of the approach. Taken together these chapters exhibit the mode as well as the trend used by the group to realize its interest. The study provides exceptional information on SIS' reform plans that have led to few public concerns which have been discussed in this study.